Budgets of families of collective farmers of the USSR in 1958–1964 (based on unpublished statistics from 1965) - Chirkov, Mikhail Сергеевич (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The article analyzes statistical data, closed for many decades to the average user, on the budgets of families of peasant farmers in 1958-1964. Analyzing these materials, it can be concluded that the situation of the collective farm peasantry of the USSR has not undergone significant changes. Monetary incomes increased slightly, while income from personal household holdings decreased as a result of government policy restrictions. The consumption of various types of agricultural products had no upward trends. The financial situation of collective farmers in 1958-1964 remained difficult.